Perspective of Gestalt Theory and Art Education - Kılıç, Ahmet Göktuğ; Parsıl, Ümit (Journal of Pedagogy and Education Science, 2024)
The perspective of art education is discussed in the context of Gestalt perception theory, and its necessity is emphasized. Undeniably, the Gestalt principle of perceptual organization and the concepts of perceptual illusion play an active role in forming motor skills and representing different points of view by activating perceptual processes such as creative and multidimensional thinking in art. Gestalt theory occupies an essential place in educational research. The Gestalt theory of perception supports holistic learning. In this sense, the goals to be achieved in art education are also crucial for the student. In visual perception, the cognitive orientation of the individual towards stimuli may vary from person to person. Approaching the same inspiration from a different angle can lead to misinterpretations of the trigger and affect learning. Although the reflections of Gestalt theory influence this view, it is considered the acceptance on which cognitive approaches are based. The basic understanding of thinking that underlies Gestalt learning theory accepts this fact and supports this fact with its underlying features. Cognitive thinking activities and perceptual orientations have an indirect effect on Gestalt theory. At the same time, the Gestalt theory and the resulting psycho-perceptual intuition have been evaluated and applied by many scientists and thinkers. Developed and presented theoretically by Max Wertheimer, Kurt Kofka, and Wolfgang Köhler, Gestalt theory led to the emergence of a new vision of visual perception in art education. Perceptual psychology, especially in the theories of Wertheimer, Kofka, and Köhler, offers a different perspective when approaching visual perception through illusion. In addition, the fact that Gestalt theory supports the learning and teaching process with a holistic learning approach has led to the openings from the perspective of art education and didactic in the context of visual perception because repeated learning in art education gains a new meaning and can develop positively if it is supported by holistic learning what you understand usually more meaningful and lasting. Finally, the research aims to explore the perspective of art education by highlighting the basic principles of Gestalt theory.